Inclusive Economic Empowerment through Halal Product Certification and the Development of a Culinary Center for Women-Led MSMEs in Denai Sarang Burung Village - Lubis, Arlina Nurbaity; Lumbanraja, Prihatin; Dalimunthe, Ritha F; Pujiati; Ramadani (Neo Journal of economy and social humanities, 2025)
This community engagement program aims to enhance the village’s economic self-reliance and social resilience through a participatory and collaborative approach involving women-led micro, small, and medium enterprises (MSMEs), youth, children, and the village government as key partners. The implementation stages began with village potential mapping through focus group discussions, followed by business legalization assistance including the issuance of Business Identification Numbers (NIB) and halal product certification along with training in business management, product innovation, and digital marketing. The results demonstrate a significant increase in local capacity and competitiveness: several women-owned MSMEs successfully obtained NIB and halal certificates, the process of establishing a culinary and souvenir center (Pujasera) as a hub for local product promotion was successfully initiated, and a digital marketing network was developed to expand market access, while a more child-friendly and gender-equitable village environment was fostered. These achievements confirm that a participatory and collaborative model can effectively create an inclusive, competitive, and sustainable village ecosystem, while also making a tangible contribution to the advancement of knowledge.